The effect of African ancestry and mismatch-repair enzyme deficiency/microsatellite instability-high on colorectal adenocarcinoma immune gene expression - Joseph, Dimitri F.; Fu, Andrew; Flores, Ricardo E.; Sharma, Dev V.; LaComb, Joseph F.; Clark, Julie M.; Li, Ellen; Liao, Yunhan; Yang, Jie; Yu, Qi; Adams, Seidu; Ogunwobi, Olorunseun O.; et al. (Frontiers in Gastroenterology, 2025)
BackgroundPrevious analyses of bulk colon and rectal adenocarcinoma (COAD/READ) RNA-sequence data comparing African ancestry (AA) and European ancestry (EA) groups have reported differentially expressed genes related to the immune response. However, these previous analyses of AA versus EA tissues did not control for mismatch-repair enzyme (MMR)/microsatellite instability (MSI) status, which is also associated with altered expression of immune related genes, and is used to determine eligibility for immune checkpoint inhibitor therapy.MethodsTCGA-COAD-READ bulk RNA-sequence data were analyzed to identify immune related genes that were significantly associated with AA and MMR-deficient (MMR-d)/MSI-High (MSI-H) groups. Reverse transcriptase-quantitative polymerase chain reaction (RT-qPCR) assays for selected immune genes relative to two reference genes, (C1ORF43 and RAB7A) were conducted on an independent set of AA (n = 59) vs. EA (n = 59) formalin-fixed paraffin embedded (FFPE) samples enriched for MMR-d/MSI-H samples. Multiple linear regression models were employed to investigate ancestry and MMR/MSI status while controlling other variables.ResultsMultivariable regression analysis of the TCGA-COAD-READ data revealed that CXCL10 expression was lower in AA vs. EA groups and higher in MMR-d/MSI-H vs. MMR-proficient (MMR-p)/MSI-Low (MSI-L)+microsatellite stable (MSS) groups while controlling for COAD/READ location and stage. Neither COAD/READ stage or location were significant while controlling for ancestry and MMR/MSI status. CXCL10 is an important chemokine that regulates the tumor immune microenvironment. The number of AA MMR-d/MSI-H samples in the TCGA-COAD-READ dataset was too low (n = 9) to detect a significant effect of AA on CXCL10 expression across MMR/MSI status. CXCL10 mRNA levels measured by RT-qPCR in an independent set of COAD FFPE samples enriched for AA MMR-d/MSI-H samples, confirmed that CXCL10 expression was higher in MMR-d/MSI-H samples compared to MMR-p/MSI-L+MSS, however, differences in CXCL10 expression between AA vs. EA did not reach significance.DiscussionThese results did not detect significant effects of AA on CXCL10 expression across MMR/MSI status.